Hubungan Dukungan Keluarga Terhadap intensitas Perilaku Bunuh Diri Pada Mahasiswa - Apriliana Haryanto, Ruth Selvy; Amaliyah, Shofwatun (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
Due to problems that occur among students with family support which may be excessive or insufficient, students often decide to harm themselves or even choose to commit suicide due to stress, depression and so on. This condition of students is caused by a lack of support from family coverage. Among students, suicidal ideation is not a new phenomenon and often occurs among students at universities. There are many students who face severe stress and depression so they have thoughts and even take these actions. This research aims to determine the effect of family support on the intensity of suicidal behavior in students. This research method uses a quantitative approach on 60 students. The instruments used in this research used a purposive sampling technique with the Family Support Scale (FSS) scale questionnaire and the Suicide Behaviors Questionnaire - Revised (SBQ-R). The regression test was used to see the strength of the two variables between family and student support with a p value of 0.002 (p value < 0.05). Based on the explanation regarding the negative impact of depression on life, students need to have the ability to face various difficulties and have resilience and support from the family as protective factors to face challenges that minimize the impact of depression factors.